Oniticellus (Liatongus) boucomonti Balthasar, 1932 (Coleoptera: Scarabaeidae: Scarabaeinae: Oniticellini)—clarification of its taxonomic status by lectotype designation - Bezděk, Aleš; Král, David; Sládeček, František X. J. (Zootaxa, 2015)
The dung beetle Oniticellus (Liatongus) boucomonti Balthasar, 1932 was described according to an unknown number of specimens labelled “Giufu-Shan, Szechuan” [= Jinfo Shan, ca. 29°04′N, 107°18′E, Chongqing province, China]. Balthasar evidently did not dissect these specimens and simply assumed that specimens with a small horn on vertex were males and specimens without such horn but with two elevated transversal carinae on head were the females of the same species (Balthasar 1932, 1935).